Raman Spectroelectrochemical Investigations of the Leaching of Gold in Chloride and Thiosulfate Media - Ronald Woods; Gregory A. Hope; Kym Watling; Matthew I. Jeffrey (Society for Mining, Metallurgy & Exploration, 2005)
Surface enhanced Raman Spectroscopy carried out in real time has been applied to identify surface species formed during gold leaching in chloride and thiosulfate media. Chloride ion is adsorbed prior to the gold dissolution potential, but its coverage is significantly diminished at the beginning of leaching. A gold chloride band is again observed when dissolution is rapid, together with bands characteristic of AuC14- ions in solution. With thiosulfate, a thin gold sulfide layer is formed slowly in the potential region where leaching occurs. At higher potentials, thiosulfate is oxidized to sulfur and sulfate, both products being identified by Raman spectroscopy.